Digital Multimodal Literacy Model of English Language Education in Indonesian Higher Education - Sahiruddin; Emy Sudarwati; Ida Puji Lestari; Royhan Abdiel Daniswara (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2025)
This research aims to (1) examine student and lecturer perceptions regarding the importance of digital multimodal literacy, and (2) to find out best practices of integrating digital multimodal literacy in teaching English language skills. This research involved sixty students and 7 lecturers from two study programs in 2 universities who used to apply multimodal texts in developing multiliteracy at an Indonesian tertiary level. This research design incorporated both quantitative and qualitative involving a survey and focus group discussion approach. The study reveals that students and lecturers had a very good perception of the utilization of digital multimodality in in teaching English language skills. Several best practices of Digital Multimodal literacy in in in teaching English language skills is also identified.